Isolation and characterisation of chemical constituents from Myrmecodia tuberosa (RUBIACEAE) / Khong Heng Yen … [et al.]. - Khong, Heng Yen; Rasemi, Saidi (2014)
Medicinal plants have been used for centuries as remedies for human diseases as they contain components of therapeutic value. Most of the modern medications are derived originally from ancient herbal traditions. Previous studies have revealed that Myrmecodia species isolated flavanoids as the major compounds. In addition, chemical compounds derived from Myrmecodia species also exhibited interesting biological activities, including cytotoxic, antibacterial, antidiabetic and anti-cancer. It would be interesting therefore, to identify the bioactive compounds of Myrmecodia tuberosa from Sarawak and determine their anti-diabetic and antioxidant properties. This study will be conducted on the barks of Myrmecodia tuberosa.